2018
DOI: 10.1093/cid/ciy207
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and Nutritional Status Among Children With Severe Acute Malnutrition in Niger: A Prospective Cohort Study

Abstract: We assessed the relationships between nutritional status and malaria infection among children with severe acute malnutrition. Baseline nutritional status was not associated with malaria infection. Malaria infection was associated with increased weight gain and decreased linear growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 49 publications
0
35
1
Order By: Relevance
“…For malaria, especially in community-based studies, the diagnosis is unreliable because fever, one of the main symptoms of malarial disease, is unspecific. It is also not established if a low anthropometric status is a protective or a risk factor for malaria [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…For malaria, especially in community-based studies, the diagnosis is unreliable because fever, one of the main symptoms of malarial disease, is unspecific. It is also not established if a low anthropometric status is a protective or a risk factor for malaria [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] A recent prospective study found no association between nutritional status and incident malaria, but malaria at baseline was associated with greater weight gain and reduced height gain over time. 20 Here, we examined the association between anthropometry and malaria infection in a population-based sample of children younger than 5 years in a region of Niger where malnutrition and malaria are co-endemic. The study population participated in a cluster-randomized trial for trachoma and all children received mass azithromycin distribution over 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…Opinions are mixed on the role of under nutrition in susceptibility to malaria illness and mortality. [12,13] observed a strong seasonal pattern of both malaria incidence and admission to the therapeutic nutritional program,…”
Section: Exposurementioning
confidence: 99%